Optimalisasi Nilai-nilai Pancasila Pada Remaja Melalui Organisasi Karang Taruna. - Nur Syamsi Romadhon; Rizal Al Hamid (JURNAL SOSIAL Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
Pancasila as the ideology of the Indonesian nation which is the standard of life in the social sphere. It is through this society that will shape one's character or personality. a good personality is always created from a good environment, but people who come from a bad environment do not always have a bad personality. It depends on how a person positions himself. At present there are many problems with young people which will serve as the main pillars of the nation's regeneration. What if the next generation fails to realize the ideals of a progressive nation? Of course this must be minimized in such a way, so that the lofty ideals of realizing the Unitary State of the Republic of Indonesia are maintained. Therefore it is important for every individual to have high self-awareness in optimizing the practice of Pancasila values. That is how important it is to reconstruct the creativity of youth and society to continue to bring out the spirit of a new ideology. Reconstruction of youth enthusiasm and creativity can be done by updating existing programs, or by adding human resources. Human resources that are more potential and qualified in their fields. This paper uses a qualitative research method with random interview data collection techniques to several youth who are active and not active in youth organizations.